Non‐linear analysis of suspension bridges with flexible and rigid cables - Juozapaitis, Algirdas; Idnurm, Siim; Kaklauskas, Gintaris; Idnurm, Juhan; Gribniak, Viktor (Journal of Civil Engineering and Management, 2010)
One of the main problems related to the design of suspension bridges is stabilisation of their initial form. The tendency of suspension bridges to deform is generally determined by the kinematical displacements of the suspension cable caused by asymmetrical loads rather than by the elastic deformations. There are some suspension bridges when the so‐called rigid (stiff in bending) cables instead of usual flexible cables are suggested for stabilisation of their initial form. The analysis methods of such suspension bridges with rigid cables are underdeveloped. For the analysis of classical suspension bridges analytical models can be applied. However, in case of concentrated forces, the numerical techniques are preferred. The article presents analytical expressions for the calculation of internal forces and displacements of suspension bridges with a rigid cable. The article also discusses the discrete calculation model for classical suspension bridges. Published Published Online: 24 Jun 2011